Chemical kinetics - Laidler, Keith J. (New Delhi, Pearson Education, 1987)
Basic concepts of both experimental and theoretical chemical kinetics are concisely explained for those seeking a general knowledge of the subject from this well-known text, now being totally revised and updated. In addition, the book is an invaluable starting point for those embarking on research in kinetics and physical chemistry. Extensive chapter bibliographies point the way toward more detailed accounts or specialized aspects. Historical background included in both chapter introductions and biographical sketches of important researches in chemical kinetics.
Includes bibliographical references.; Index 525-531p.
Keywords: Kinetic theory; Chemistry